House-sitting at Tony's - Behling, Steve (Step into reading., 2026)
Team Spidey pays a visit to Tony Stark's home. Iron Man Tony has all sorts of gadgets! When he has to leave, it's up to Team Spidey to stop Electron from using Tony's tech to enhance his powers!